1993
DOI: 10.1248/cpb.41.1258
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antithyroid Activity of Pyridine, Pyrimidine and Pyrazine Derivatives of Thiazole-2-thiol and 2-Thiazoline-2-thiol.

Abstract: A series of compounds was synthesized by linking various derivatives of pyridine, pyrimidine or pyrazine to thiazole-2-thiol or to its partially hydrogenated derivative 2-thiazoline-2-thiol. The reactions of the compounds with molecular iodine and lactoperoxidase were examined in vitro. Their antithyroid activity was also examined in vivo in the rat. T4 and TSH levels were determined, and the thyroid gland was examined histologically. 2-(3-Hydroxy-2-pyridyl)-2-thiothiazoline had the highest antithyroid activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…While halogen bonding involving the halogenated thyroid enzymes is often the focus of studies in this area, the role of I 2 is also of interest [17,18]. Closely related to this are investigations into the interaction of various antithyroid drugs with I 2 [19].…”
Section: Significance Of Halogen Bonding With Dihalogensmentioning
confidence: 99%
“…While halogen bonding involving the halogenated thyroid enzymes is often the focus of studies in this area, the role of I 2 is also of interest [17,18]. Closely related to this are investigations into the interaction of various antithyroid drugs with I 2 [19].…”
Section: Significance Of Halogen Bonding With Dihalogensmentioning
confidence: 99%
“…Hence, MMI and PTU are the only basic drugs, which have their own limitations and side effects (Bandyopadhyay et al, 2002). Scarcity of medicines for the treatment of hyperthyroidism motivated the workers to look for alternate drugs (Lagorce et al, 1993). During such efforts certain synthetic compounds like 2,3-dihydroxypyridine (Abou-Shaaban et al, 1995), and 1-cyclohexyl-3-(3-quinolyl)-2-thiourea (Laurence et al, 1998), are found to exhibit antithyroid activity.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, antithyroid activity of a number of synthetic and natural compounds was studied. 3 Synthetic antithyroid agents may either act by making stable complexes with iodine or by interfering with thyroid peroxidase (TPO) enzyme. In the first mechanism they make stable electron donoracceptor complexes with molecular iodine produced by the oxidation of iodides, diverting the oxidized iodides away from thyroglobulin and ceasing the biosynthesis of thyroid hormones (T 3 and T 4 ).…”
Section: Introductionmentioning
confidence: 99%